(untitled) (Journal of the College of Basic Education, 2022)
Basketball occupies a distinguished position in the world, like other sports, and it still enjoys popularity and public admiration among sports practitioners. Related to the sports side, which deals with the impact of regular training on each of the musculoskeletal system, the nervous system, and the circulatory system, through developing the efficiency of these devices and raising their capabilities in facing performance conditions, and this is the main goal of any training curriculum.